In-between Hope and Uncertainty: Phenomenon of Quality of Life among Young Adult Hemodialysis Patients - Jam Gabrielle Ramos Cani; Aya Mushu; Hyacinth Ansel Mae Añez; Jemerson Dominguez (Journal of Health and Behavioral Science, 2025)
End-stage renal disease (ESRD) signifies the final stage of chronic kidney disease (CKD), often necessitating kidney transplants or hemodialysis for survival. Hemodialysis imposes significant limitations on patients' daily lives, potentially leading to psychological issues. Prior studies have examined hemodialysis patients' experiences and quality of life, but the Philippine context, particularly among young adults, remains understudied. This research aims to describe the lived experiences of young adult hemodialysis patients, understand their perceptions of life-and-death risks, and explore changes in their quality of life and mental health. The study employed descriptive phenomenological research with thematic analysis, involving five young adult patients undergoing hemodialysis. Themes such as difficulty understanding their situation, dealing with life’s difficulties, life of uncertainty, and psychological impacts emerged from the data which provided insight into the experiences of young adult patients. Understanding these experiences can enhance care, support, and overall quality of life for young adult hemodialysis patients.